1998
DOI: 10.1093/ajcn/67.2.301
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of dietary fatty acids on the fatty acids of human milk

Abstract: Although it is known that the fatty acid profile of human milk is altered by diet, the rapidity with which this occurs has not been addressed. We hypothesized that after absorption the fatty acids of a given meal would be transferred rapidly from the chylomicrons of the blood into human milk. Fourteen lactating women drank six test formulas, each containing a different fat: menhaden oil, herring oil, safflower oil, canola oil, coconut oil, or cocoa butter. The subjects collected a midfeeding milk sample before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
87
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 20 publications
7
87
2
Order By: Relevance
“…The synthesis of DHA from alpha-linolenic acid occurs slowly, and the feeding of alpha-linolenic acid in humans does not produce an appreciable increase in plasma or breast milk DHA (31)(32)(33). Dietary alpha-linolenic acid was ultimately effective at reversing most of the biochemical deficiency in rhesus monkeys in the current long-term study.…”
Section: Discussionmentioning
confidence: 72%
“…The synthesis of DHA from alpha-linolenic acid occurs slowly, and the feeding of alpha-linolenic acid in humans does not produce an appreciable increase in plasma or breast milk DHA (31)(32)(33). Dietary alpha-linolenic acid was ultimately effective at reversing most of the biochemical deficiency in rhesus monkeys in the current long-term study.…”
Section: Discussionmentioning
confidence: 72%
“…In this study, maternal administration of Wy during the lactation period triggers DNA demethylation of the fatty acid b-oxidation genes, suggesting that DNA demethylation in the neonatal liver can be controlled by the PPARa ligands delivered to the pup via breast milk. Evidence has suggested that the fatty acid composition of breast milk is affected by maternal nutritional condition (35,36). It is reported that PPARa serves as an adaptive mechanism to nutritional changes such as an excess of lipid intake and fasting (8).…”
Section: Discussionmentioning
confidence: 99%
“…The DHA amount in the mother's milk is variable, and depends on the mother's diet. The American and European women's milk contains about 0.15 to 0.3% of DHA (Dontson et al, 1992;Birch et al 1998;François et al, 1998), while, in other parts of the world, the DHA amount in the mother's milk can reach 0.1 to 1.4% of the total fatty acids (Innis, 1992). The ω-3 fatty acids are essential for the development of nerve cells, neurons and glial cells.…”
Section: Qidqw Ghyhorsphqwmentioning
confidence: 99%